Persepsi Masyarakat Desa Ngaglik, Sleman Terhadap Pemanfaatan Air Hujan Sebagai Media Pengobatan: Manfaat dan Risiko Kesehatan - Nurfadila, Ainaya; Husain, Fadly (Universitas Lambung Mangkurat, 2026)
Rainwater is a natural resource that has great potential not only as an alternative to clean water, but also as a medium for health therapy. However, its use as a medium for traditional medicine still raises debates regarding its safety and scientific validity. This study aims to analyze public perceptions, perceived benefits, and understood health risks related to the use of rainwater as a medium for traditional medicine. This study uses a qualitative approach with a case study design conducted in Ngaglik, Sleman, Yogyakarta. Data were collected through observation, in-depth interviews, and documentation, then analyzed descriptively and interpretively. The results show that public acceptance of rainwater therapy tends to increase, mainly influenced by economic factors, education levels, personal experiences, and community social influences. Although there are still doubts regarding the safety of rainwater consumption, a scientific approach through Total Dissolved Solids (TDS) measurements and user testimonials are important factors in building public trust. This study confirms that evidence-based education and appropriate scientific communication play a significant role in strengthening the legitimacy of local wisdom-based medical practices.